2003
DOI: 10.1097/01.ccm.0000063040.24541.49
|View full text |Cite
|
Sign up to set email alerts
|

Cytochrome P450 3A4 activity after surgical stress

Abstract: Acute inflammation after elective surgery was associated with a significant decline in cytochrome P450 3A4 activity, which is predictive of clinically important changes in the metabolism of commonly used drugs that are substrates for this enzyme.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
53
1
2

Year Published

2004
2004
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(61 citation statements)
references
References 55 publications
5
53
1
2
Order By: Relevance
“…Therefore, the lower concentration part (1-100 pg/mL) of the whole doseresponse curve data was used to estimate the induction effect of IL-6 on CYP1A2 in healthy subjects and in RA patients. This concentration range covered the average baseline IL-6 concentration ranges in both healthy subjects (1.24-6.56 pg/ ml) (16,17,(20)(21)(22)(23)(24)(25)(26) and those in RA patients (3.51-119 pg/mL) (8,10,(14)(15)(16)(17)(18)(19)(20). The PBPK simulation results using the estimated E max and EC 50 value of IL-6 on CYP1A2 induction reasonably captured the moderate modulation effect of IL-6 on caffeine PK in RA patients (Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, the lower concentration part (1-100 pg/mL) of the whole doseresponse curve data was used to estimate the induction effect of IL-6 on CYP1A2 in healthy subjects and in RA patients. This concentration range covered the average baseline IL-6 concentration ranges in both healthy subjects (1.24-6.56 pg/ ml) (16,17,(20)(21)(22)(23)(24)(25)(26) and those in RA patients (3.51-119 pg/mL) (8,10,(14)(15)(16)(17)(18)(19)(20). The PBPK simulation results using the estimated E max and EC 50 value of IL-6 on CYP1A2 induction reasonably captured the moderate modulation effect of IL-6 on caffeine PK in RA patients (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Literature data regarding systemic levels of IL-6 were pooled together to determine the population mean with SD for systemic levels of IL-6 in RA patients (8,10,(14)(15)(16)(17)(18)(19)(20) and in healthy subjects (16,17,(20)(21)(22)(23)(24)(25)(26). The mean or individual IL-6 plasma or serum concentration values from different studies were combined, and associated variability was calculated with R (http://www.r-project.org) and Excel (Microsoft, Redmond, WA).…”
Section: Pooled Analysis Of Systemic Il-6 Concentrations In Ra Patienmentioning
confidence: 99%
“…Moreover, bacterial respiratory infections, as well as chronic obstructive lung disease, reduce the ability of the organism to clear xenobiotics (Sonne et al, 1985). Other causes of inflammation, such as elective surgery, reduce the activity of CYP3A4 (Haas et al, 2003). Using animal models, it has been shown that various models of inflammation, such as the injection of lipopolysaccharide (LPS), turpentine, and carrageenan depress the activity of the P450 (Cheng and Morgan, 2001;Renton, 2001).…”
mentioning
confidence: 99%
“…So ist beispielsweise bekannt, dass der H 2 -Antagonist Cimetidin oder der bei HIV-Infektion eingesetzte Proteinasehemmer Ritonavir Inhibitoren der CYP3A4 sind und daher die Eliminationszeit der Substanzen Fentanyl, Sufentanil und Alfentanil verlängert sein kann.Auch Erythromycin und Propofol können die pharmakokinetischen Eigenschaften von Alfentanil durch Interaktion mit der CYP-450-abhängigen Elimination beeinflussen [25,44]. Zudem kann es im Zusammenhang mit chirurgischen Interventionen und der damit verbundenen Inflammation zu einer Abnahme der Aktivität des CYP 3A4 kommen [21].…”
Section: Metabolisierung Der Opioideunclassified